2007
DOI: 10.1111/j.1742-4658.2007.06070.x
|View full text |Cite
|
Sign up to set email alerts
|

Aplysia temptin − the ‘glue’ in the water‐borne attractin pheromone complex

Abstract: Pheromones play an important role in coordinating male and female reproductive behavior in many aquatic species. Strikingly, however, relatively few peptide or protein pheromones have been characterized in invertebrates or vertebrates, as they are often difficult to isolate in sufficient quantities to characterize either biochemically or behaviorally. Furthermore, as we have seen with the marine mollusk Aplysia, protein pheromones require interaction with other proteins to exert their effect. Egg laying in Apl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…glabrata proteins from snail conditioned water (SCW) and following electrostimulation (ES), which induces rapid release of proteins. The detection by NanoHPLC-MS/MS of an orthologue of temptin, a pheromone of Aplysia 12, among these proteins (Supplementary Note 5; Supplementary Data 10) suggests an operational pheromone sensory system in B . glabrata .…”
Section: Resultsmentioning
confidence: 99%
“…glabrata proteins from snail conditioned water (SCW) and following electrostimulation (ES), which induces rapid release of proteins. The detection by NanoHPLC-MS/MS of an orthologue of temptin, a pheromone of Aplysia 12, among these proteins (Supplementary Note 5; Supplementary Data 10) suggests an operational pheromone sensory system in B . glabrata .…”
Section: Resultsmentioning
confidence: 99%
“…Copper ion binding (GO:0005507) is another molecular function enriched in the secretome. The pheromone activity (GO:0005186) enriched in the secretome is found in proteins similar to temptins, which mediates protein-cell surface contact during fertilization in mollusks [49]. A Phospholipase D (PLD) motif (PF00614) is among the Pfam domains enriched in the P. infestans secretome.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the N-terminal of both the Pomatoceros and Aplysia proteins are only conserved with a different Aplysia protein, the pheromone temptin [GenBank: AAS92605] [53] and with a gene predicted from the genome of the basal metazoan lineage Trichoplax [GenBank: XP_002117562]. The function and structure of Aplysia temptin have been analysed in detail, and the central 1 region of temptin (squared with red lines in Figure 4C) as well as two disulfide bonds (shown by red lines and triangles in Figure 4C) determined by a structure analysis using recombinant temptin [54] are well conserved amongst these genes. We have found that this unique combination of the temptin and mono-oxygenase sequences is also present in the Lottia genome [JGI: jgi|Lotgi1|192843|estExt_Genewise1.C_sca_480139] but is not found outside the Lophotrochozoa.…”
Section: Resultsmentioning
confidence: 99%